Fatores associados ao status de vitamina D em indivíduos com insuficiência cardíaca residentes em uma região ensolarada - Komatsu, Raquel Costa Silva Dantas (2018)
Hypovitaminosis D has been a frequent finding in individuals with heart failure (HF), however studies in regions with high solar incidence are scarce. The aim of this study was to evaluate the vitamin D status and its associated factors in individuals with HF living in a sunny region. This cross-sectional study was conduced with 70 adult and elderly individuals diagnosed with HF, according to the Boston points system and the Framingham criteria, confirmed by the Doppler echocardiogram. Clinical, biochemical, anthropometric, dietetic data, skin phototype, sun exposure and physical activity were evaluated. 25-hydroxyvitamin D (25OHD) was analyzed by electrochemiluminescence immunoassay method. Subjects were agruped according to 25OHD concentrations in "sufficient" (≥30ng / mL) and "hypovitaminosis D" (<30ng / mL). Comparisons of the variables between groups were performed using appropriate statistical tests. Correlations between 25OHD concentrations and continuous variables were assessed by the Pearson or Spearman coefficient (r). The relationship between the independent variables and the 25OHD concentration was adjusted accordingly using the generalized linear regression model. The individuals had a mean age of 53 (15) years, predominantly male (64.3%). The mean concentration of 25OHD was 40.1 (12.4) ng / mL, with 24.3% of hypovitaminosis D. A significantly higher frequency of females was observed in the hypovitaminosis D group [Odds Ratio (OR) = 7.38; p = 0.001]. Participants who presented HF with ischemic etiology had a higher risk for hypovitaminosis D (OR = 3.97, p = 0.03), as well as those with high PTHi (> 67pg / mL) (OR = 3.39, p = 0.034 ). Subjects who did not use angiotensin II receptor antagonists / angiotensin converting enzyme inhibitors (ARA / ACEI) and those using platelet antiplatelet drugs had a significantly higher chance for hypovitaminosis D (OR = 11.14, p = 0.015 and OR = 5.81, p = 0.003, respectively). Significant correlations were found between 25OHD and albumin (r = 0.365, p = 0.015), total calcium (r = 0.266, p = 0.026), hemoglobin (r = 0.249, p = 0.037), TGP 0.002) and PTHi (r = -0.255, p = 0.033). Analysis of the regression model adjusted for 25OHD showed that sex is an independent predictor of 25OHD concentrations, with 25OHD concentrations being higher in males compared to females (β = 7.78, p = 0.005). The New York Heart Association (NYHA) functional classification also proved to be an independent predictor, and NYHA I subjects were found to have 25OHD concentrations higher when compared to NYHA class III / IV (β = 8.23; p = 0.032). It was concluded that the majority of individuals with HF residing in a sunny region had sufficient 25OHD status. Sex and functional classification are independent predictors of 25OHD.